Genera of Spore-Feeding Thysanoptera from Southeast Asia (Phlaeothripidae, Idolothripinae), with a species checklist from Peninsular Malaysia - Eow, L. X.; Mound, L. A.; Ng, Y. F. (Zootaxa, 2011)
An illustrated key is provided to the 31 genera of the subfamily Idolothripinae recorded from Southeast Asia, and a checklist provided to 34 species recorded from Peninsular Malaysia. Notes are given on the habitat preferences of these fungal spore-feeding thrips, together with for each genus some discussion of systematic relationships and species diversity.